FORMULASI EKSTRAK ETANOL DAUN ALPUKAT (Persea americana Mill) DAN DAUN SIRIH (Piper betle) SEBAGAI REPELLANT (ANTI NYAMUK) BERBENTUK MAT ELEKTRIK TERHADAP NYAMUK Aedes aegypti - Yunus, Arifuddin; Wahyuni, Dwi Fitrah; Nurzak, An Nisaa (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
The epidemiology and area of the spread of DHF is increasing along with the increasing mobility and population density. One of the efforts made in eradicating mosquito vectors is by using insecticides. This study aimed to examine the effectiveness of the combination of avocado (Persea americana) and betel leaf (Piper betle) ethanol extracts against the death of Aedes aegypti mosquitoes. This study aimed to examine the effectiveness of the combination of avocado (Persea americana) and betel leaf (Piper betle) ethanol extracts against the death of Aedes aegypti mosquitoes. This research design is experimental with post test only control group design. The electric mat that had been soaked with a combination of ethanolic extract of avocado (Persea americana) and ethanolic extract of betel leaf (Piper betle) was divided into 4 concentration groups, namely positive control, negative control, and a combination of extracts with concentrations of 1%, 3% and 5 %. Then tested with 10 Aedes aegypti mosquitoes in each treatment. Then tested with 10 Aedes aegypti mosquitoes in each treatment. The results showed that at a concentration of 5% it was able to kill 10 Aedes aegypti mosquitoes in just 5 minutes compared to concentrations of 1% and 3%. From this study it can be concluded that the greater the concentration of extract used, the faster the duration of time to kill the Aedes aegypti mosquito.